1997
DOI: 10.1056/nejm199702133360702
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Ostial Renal-Artery Stenoses with Vascular Endoprostheses after Unsuccessful Balloon Angioplasty

Abstract: Accurate placement of renal-artery stents is technically feasible without major complications. The favorable early and long-term results suggest that primary stent placement is an effective treatment for renal-artery stenosis involving the ostium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
262
5
22

Year Published

1998
1998
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 488 publications
(302 citation statements)
references
References 43 publications
13
262
5
22
Order By: Relevance
“…According to single center reports, revascularization could stabilize or at least slow the decline of renal function and improve blood pressure control [21 -23]. However, curing hypertension by means of angioplasty or stenting of atherosclerotic RAS rarely occurs, although the number of antihypertensive medications can usually be reduced after successful revascularization [24,25]. Three randomized controlled trials on the eff ects of balloon angioplasty compared to medical treatment of RAS in hypertensive patients were negative regarding improved blood pressure control following revascularization [5 -7], whereas a meta-analysis of those three trials resulted in signifi cantly lower blood pressure values in the angioplasty cohort [26].…”
Section: Discussionmentioning
confidence: 99%
“…According to single center reports, revascularization could stabilize or at least slow the decline of renal function and improve blood pressure control [21 -23]. However, curing hypertension by means of angioplasty or stenting of atherosclerotic RAS rarely occurs, although the number of antihypertensive medications can usually be reduced after successful revascularization [24,25]. Three randomized controlled trials on the eff ects of balloon angioplasty compared to medical treatment of RAS in hypertensive patients were negative regarding improved blood pressure control following revascularization [5 -7], whereas a meta-analysis of those three trials resulted in signifi cantly lower blood pressure values in the angioplasty cohort [26].…”
Section: Discussionmentioning
confidence: 99%
“…Stenting cured hypertension in 0-16%, with improvement (mean reduction of half of one hypotensive drug) in around half of patients. 19,25,26 Even the modest improvement in blood pressure may be overestimated in these uncontrolled studies as recorded blood pressure in patients with RVH spontaneously falls with follow up. 28 Three prospective randomised controlled trials comparing PTRA +/− stenting have recently reported.…”
Section: Does Revascularisation Beneficially Affect Hypertension or Rmentioning
confidence: 97%
“…Several series report initial technical success of over 90% with less than 20% restenosis over 2 years. 5,19,[24][25][26] A clear benefit of revascularisation over medical management of atheromatous renovascular hypertension has not been demonstrated. Ramsay reviewed 10 uncontrolled series of PTRA for atheromatous RVH.…”
Section: Does Revascularisation Beneficially Affect Hypertension or Rmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] While restenosis occurs in > 50% of patients treated with percutaneous transluminal renal angioplasty, 9-11 restenosis rates of renal artery stents are only 10-25%. [2][3][4][5][6] As expected, the risk of renal artery stent restenosis is related to stent diameter, with larger stent diameters having lower rates of restenosis.…”
Section: Case Reportmentioning
confidence: 99%
“…Renal artery stenting is the procedure of choice for treating atherosclerotic renal artery stenosis. [1][2][3][4][5][6][7][8] However, long-term benefits of renal artery stenting may be blunted by the development of stent restenosis, and the treatment of this condition is not well established, with limited therapeutic options. We present a case report of intravascular ultrasound-guided cutting balloon angioplasty (CBA) as a novel technique for the treatment of renal artery stent restenosis.…”
Section: Introductionmentioning
confidence: 99%